2020
DOI: 10.3390/w12020500
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Water Quality Elements of Water Bodies and the Hydrometric Parameters: Case Study in Lithuania

Abstract: The larger and deeper lakes and ponds are, the better the conditions for spontaneous water purification, slower hydrobiological processes and slower accumulation of sediment. The goal of this research was to assess the ecological status of selected Lithuanian lentic water bodies and the impact of morphometric indicators on water quality. Multiple studies were conducted on 29 lakes and 10 ponds located throughout Lithuania in 2014–2018. The study proved that higher maxima and average depths of lakes correlate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Previous study reported that highest phytoplankton abundance Lake Cibuntu and Lake lotus was found in August and September respectively [20]. The variability of dissolved oxygen (DO) in Lake Cibuntu, Lake Lotus and Lake Dora may be related to the changes of hydro morphological (water depth, water volume) and hydrobiological processes (overgrowth of phytoplankton and metabolism proses) in lake [21]. The stable value of dissolved oxygen (DO) concentration in Lake Cibuntu, Lake Lotus and Lake Dora in high water depth (November to December 2018) indicated a stability of biotic community in those periods.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study reported that highest phytoplankton abundance Lake Cibuntu and Lake lotus was found in August and September respectively [20]. The variability of dissolved oxygen (DO) in Lake Cibuntu, Lake Lotus and Lake Dora may be related to the changes of hydro morphological (water depth, water volume) and hydrobiological processes (overgrowth of phytoplankton and metabolism proses) in lake [21]. The stable value of dissolved oxygen (DO) concentration in Lake Cibuntu, Lake Lotus and Lake Dora in high water depth (November to December 2018) indicated a stability of biotic community in those periods.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Nielisz Reservoir is clearly larger than the remaining reservoirs (average water retention time is 77 days), which might have a positive effect on the degree of mineralisation of matter suspended in its waters. In large and deep reservoirs, the transport of organic matter to the bottom takes place over a longer interval of time, so the process of its mineralisation is more efficient than in small and shallow reservoirs [ČESONIENĖ et al 2020;WOJTKOWSKA, DMOCHOWSKI 2009].…”
Section: Discussionmentioning
confidence: 99%
“…pacity [63]. However, during the long-term monitoring, the water quality remained in the range of Class IV water standards (China Environmental Quality Standard for surface water.…”
Section: Potential Pollution Source Analysismentioning
confidence: 99%
“…For example, Kim et al The levels of water quality parameters in Region A were maintained at moderate levels. This might be because Region A is an inlet to the Chaohu Lake with a wide watercourse and strong liquidity and the water body has relatively higher self-purification capacity [63]. However, during the long-term monitoring, the water quality remained in the range of Class IV water standards (China Environmental Quality Standard for surface water.…”
Section: Compare With Other Studiesmentioning
confidence: 99%